Pools or schools or both? Diversification and specialisation in public services - Daniel Dujava; Tomáš Černěnko; Oliver Rafaj (University of Economics in Bratislava, Department of Economic Policy, 2019)
We develop a model of two municipalities providing two public services. We show that in case of intermediate level of transferability of public services between two municipalities, Pareto-suboptimal Nash equilibrium exists. In this case, cooperation between municipalities or merging of two municipalities into one unit would improve welfare.
Keywords: C72; H11; 330; diversification; game theory; public services; specialisation